Simple and Direct Synthetic Route to a Rod-Coil Conjugated Block Copolymer from Either a Rod or Coil Block Using a Single Bifunctional Initiator: A Solvent Dependent Self-Assembly and Field Effect Mobility Study - Daripa S.; Khawas K.; Sharma A.; Kumar A.; Pal B.; Das S.; Jit S.; Kuila B.K. (My University, 2025)
Here, we have described a simple and straightforward methodology for synthesis of rod-coil conjugated block copolymer poly(3-hexylthiophene)-block-polystyrene (P3HT-b-PS) of varying molecular weight and low polydispersity by chain extension of either a rod or coil block starting from a single bifunctional initiator through combination of Kumada catalyst transfer polymerization (KCTP) and atom transfer radical polymerization (ATRP). Advantages of the present method include the facile synthesis of the Ni(II) catalytic initiators from readily available laboratory reagents, avoiding high reactive intermediates for preparing Ni(ii) catalytic initiator, and the in situ nature of all the steps making large scale preparation of the block copolymer viable. Studies on solvent-induced structure formation and their impact on optical and electronic properties of the block copolymer were systematically performed. The block copolymer device fabricated from toluene shows the best field effect mobility of (2.1 ± 0.75) × 10-3 cm2 V-1 s-1 compared to results for other solvents. Overall, this work describes a facile synthetic strategy for a rod-coil conjugated block copolymer and its solvent-induced structure formation as guidance for fabricating high-performance organic electronic and optoelectronic devices. Copyright © 2020 American Chemical Society.